Internal Transformation and Civil Servant Performance: Examining the Mediating Role of Job Satisfaction in Indonesia's Ministry of Health. - Suprianto; Slamet Ahmadi; Titing Widyastuti; Besar Agung Martono (www.amertainstitute.com, 2026)
Background: Public organizations face increasing pressure to enhance organizational performance amid rapid technological change, accountability demands, and evolving citizen expectations. Internal transformation has consequently become a strategic mechanism for improving employee performance. However, limited empirical evidence explains how different dimensions of internal transformation influence civil servant performance and whether job satisfaction serves as an underlying mechanism, particularly in developing-country public sector organizations. Objective: This study examines the effects of Internal Transformation, operationalized through Effective Execution, New Ways of Working, and Service Excellence, on Civil Servant Performance, with Job Satisfaction as a mediating variable at the Secretariat General of the Indonesian Ministry of Health. Methods: A quantitative explanatory approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from civil servants at the Secretariat General of the Ministry of Health. The analysis assessed reliability, convergent and discriminant validity, collinearity, structural relationships, mediation effects, and predictive relevance. Results: Effective Execution significantly enhances Job Satisfaction, while Service Excellence demonstrates the strongest direct effect on Civil Servant Performance. New Ways of Working does not significantly affect performance directly. Furthermore, Job Satisfaction has no significant effect on Civil Servant Performance and does not mediate the relationships between internal transformation dimensions and performance. Conclusion: Internal transformation affects civil servant performance unevenly across dimensions. Service Excellence emerges as the most influential determinant, highlighting the importance of context-specific organizational mechanisms in public sector transformation.